PENGARUH PEMBELAJARAN SEKOLAH LIMA HARI, KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA XII PEMASARAN SMK NEGERI 1 SURAKARTA AJARAN 2018/2019 - -, Putri Pertiwi Ningrum -; -, Sri Wahyuni -; -, Salman Alfarisy Totalia - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
This study aims to determine whether or not there is (1) the influence of the five day school learning system and learning independence together on the learning achievement of the XII Marketing class students of SMK Negeri 1 Surakarta in the Academic Year 2018/2019; (2) the influence of the five day school learning system on student achievement in Marketing XII class of SMK Negeri 1 Surakarta Academic Year 2018/2019; (3) the effect of learning independence on students' achievement in Marketing Class XII of SMK Negeri 1 Surakarta in Academic Year 2018/2019.The population in this study were Marketing XII grade students of SMK Negeri 1 Surakarta Academic Year 2018/2019 with a total of 57 students. This study uses a samling saturated type Non Probability Sampling technique, so that the number of samples is equal to the number of population, there are 57 students who are sampled. The research method used is a quantitative method. Data collection is done using questionnaires / questionnaires, interviews and documentation for five day school learning system data, learning independence and learning achievement. This study uses data analysis namely multiple regression with a significance level of 0.05, then processing data that has been obtained with the help of the SPSS data program (Statistical Product and Service Solution) version 22.The results showed that: first, there was a positive and significant influence between the five day school learning system on the learning achievement of Marketing XII students at SMK Negeri 1 Surakarta in the Academic Year 2018/2019, as indicated by the tcount = 2.440> t table = 2.003. Second, there is a significant positive effect between learning independence on the learning achievement of Marketing XII students at SMK Negeri 1 Surakarta in the Academic Year 2018/2019, as indicated by the value of tcount = 6.424> t table = 2.003. Third, there is a significant effect of the five day school learning system and learning independence together on the learning achievement of the XII Marketing class of SMK Negeri 1 Surakarta in the Academic Year 2018/2019, as shown by Fcount = 21,153> Ftable = 3,168.